27. ELECTRONIC HEALTH LITERACY AMONG MEDICAL STUDENTS AT DAI NAM UNIVERSITY (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the level of electronic health competence among medical students at DaiNam University and related factors.Research Object and Method: The study utilized a descriptive research design. The researchersassessed the electronic health competence of medical students using an eHealth score ranging from8 to 40. We collected data on students’ knowledge of medical resources available on the Internet,ability to find helpful information, familiarity with reliable sources, utilization of the Internet forhealth information, skills to evaluate online medical information, ability to distinguish the quality ofmedical information, confidence in using the Internet for health decision-making, and search habits.Statistical analysis was conducted to determine any significant differences among different groups.Results: The average eHealth score of the study subjects was 28.9 ± 4.8. The majority of the studentsagreed or strongly agreed that they knew medical resources available on the Internet (65.5%), knewwhere to find helpful information (68%), were familiar with useful sources (68.5%), knew how to usethe information on the Internet to answer health-related questions (70.9%) and use this informationto help themselves (70.9%). However, only 63.5% of students felt they had the necessary skills toevaluate medical information online, and only 8.6% were confident in their ability to distinguish thequality of medical information online. Additionally, 50.8% of students felt satisfied using data fromthe Internet to make health decisions. Students who frequently searched for medical informationfor study and research purposes, found leads in scientific journals, through Medline, Pubmed, andreputable medical organizations’ websites, and had the habit of reading the information in scientificjournals or social networks had significantly higher average electronic health competence scorescompared to other groups (p
Keywords: Electronic health literacy, medical students, students, Dai Nam University, DNU.